2012
DOI: 10.1038/nmat3404
|View full text |Cite
|
Sign up to set email alerts
|

Macroporous nanowire nanoelectronic scaffolds for synthetic tissues

Abstract: The development of three-dimensional (3D) synthetic biomaterials as structural and bioactive scaffolds is central to fields ranging from cellular biophysics to regenerative medicine. As of yet, these scaffolds cannot electrically probe the physicochemical and biological micro-environments throughout their 3D and macroporous interior, although this capability could have a marked impact in both electronics and biomaterials. Here, we address this challenge using macroporous, flexible and free-standing nanowire na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
607
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 585 publications
(627 citation statements)
references
References 44 publications
3
607
0
3
Order By: Relevance
“…In its essence, “cyborganics” represents an emerging concept at the crossroads of tissue engineering, materials science, electronics, and chemistry with the daring aim to create a new class of hybrid organs and hydrogel carriers made from a combination of inanimate and biological matter 17, 18, 427. Cyborganics can be divided into two different classes:427 i) permanent hybrid organs consisting of stable matter and living tissue and ii) hydrogel carriers embedded with biological matter and degradable nanomaterials with the grand goal of regenerating dysfunctional tissues.…”
Section: Cybernetic Prostheticsmentioning
confidence: 99%
“…In its essence, “cyborganics” represents an emerging concept at the crossroads of tissue engineering, materials science, electronics, and chemistry with the daring aim to create a new class of hybrid organs and hydrogel carriers made from a combination of inanimate and biological matter 17, 18, 427. Cyborganics can be divided into two different classes:427 i) permanent hybrid organs consisting of stable matter and living tissue and ii) hydrogel carriers embedded with biological matter and degradable nanomaterials with the grand goal of regenerating dysfunctional tissues.…”
Section: Cybernetic Prostheticsmentioning
confidence: 99%
“…14 Although bio-mimetic enzyme-based electrical sensors are attractive tools, their use on a robust lab-on-a-chip platform with fast, sensitive and stable three-dimensional (3D) porous interfaces for localized real-time, long-term monitoring of cellular activities and physicochemical changes have not been demonstrated. [15][16][17][18][19] Inspired by insect tentacles, herein, we developed an unconventional antenna-like heterostructure based on direct growth of porous PB nanocube heads on the tips of TiO 2 nanowire (NW) arms, which can be used for 3D interface recognition and biosensing. Singlecrystalline TiO 2 NWs are first hydrothermally grown on conducting substrates, followed by the direct growth of nanoporous PB nanocubes on the tips of the TiO 2 NW arrays via an etching and seed-assisted process ( Figure 1, Supplementary Figure S1).…”
Section: Introductionmentioning
confidence: 99%
“…Such a study is difficult but immensely useful because the hybrid (metal-semiconductor) nanostructures can be used for a wide range of applications such as SERS, [16][17][18] photonics, 4,5 renewable energy 3 and biomedicine. [19][20][21] This study addresses whether the newly observed optical effects, LMR and SWs in an NW system, can positively affect the plasmonic E field for photonic applications.…”
Section: Introductionmentioning
confidence: 99%